Usage of compaction simulators for the powder compression characterization – advantages and limitations - Nikolić, Nenad; Miletić, Tijana; Kovačević, Jovana; Medarević, Djordje; Ibrić, Svetlana (Archives of Pharmacy, 2022)
Compaction simulators are designed as machines which can provide an in-depth analysis of the powder compaction process. Characterization of the powder compression and compaction process, as well as material characterization, play an important role in the formulation and manufacturing process design and development, as well as in creating a strong knowledge basis for the scale-up of the tablet compression and troubleshooting in further stages of the product lifecycle. Although compaction simulators are designed to simulate the compression process on high-speed tablet-presses, with the advantages of a small quantity of material needed and highly sophisticated instrumentation, there are certain limitations in the extrapolation of the process parameters from these machines to high-speed rotary tablet presses. However, the advantage of the use of compaction simulators for studying basic compression and compaction mechanisms, identification of critical material attributes and critical process parameters ranges, and their relations with tablet characteristics and critical quality attributes of pharmaceutical products is clear, compared to the use of small excentre tablet presses, and complementary to the use of small rotary tablet presses. This scientific paper provides an overview and examples of the different advantages provided by the instrumentation of compaction simulators, including certain limitations in their exploitation.
Keywords: compaction simulator; tablet-press instrumentation; scale-up; compressibility; compression block deformation